PENERAPAN MODEL EXPERIENTAL LEARNING UNTUK MENINGKATKAN HASIL BELAJAR POKOK BAHASAN UNSUR LINGKARAN SISWA KELAS VIII SMP SALAFIYAH MIFTAHUL HUDA JENGGAWAH TAHUN AJARAN 2012/2013 - Azizi, Alfan; Susanto, S; Pambudi, Didik Sugeng (KadikmA, 2013)
Abstract. One of the factors that caused students less comprehension to subject material is students were not guided to find the concepts of taught material. During this time, most of the teachers more used Classical Learning by using Tutorial Method and Cooperative Learning Model that only applied Discussion and Question Answer Method without guided the students to find the concepts of the taught material. Experiential Learning model is one of the learning model that can be used to overcome the problem. This learning model consists of four steps. The steps are Concrete Experience (CE), Reflection Observation (RO), Abstract Conceptualization (AC), and Active Experimentation (AE). This research design was Classroom Action Research (CAR) used two cycles. Every cycle consists of twice learning and once test in the last. The research that had been done in SMP Salafiyah Miftahul Huda Jenggawah Jember showed that the students learning achievement on Circle Elements theme used the implementation of Experiential Learning Model got increased. Key Words : Experiential Learning Model, Learning Achievement, Circle Elements